Analysis of aristolochic acids in Houttuynia cordata by liquid chromatography–tandem mass spectrometry. (25th September 2020) - Chan, Chi‐Kong; Pan, Guanrui; Chan, Wan
Abstract: Houttuynia cordata ( H. cordata ) is a popular vegetable in Asian countries and is also used extensively as herbal medicine in treating various diseases. H. cordata contains aristolactams, which have a similar Chinese name as aristolochic acids (AAs); hence, an emerging concern in the greater China region has arisen about the potential linkage between H. cordata and aristolochic acid nephropathy (AAN). However, only a single study has tested for the presence of AAs in H. cordata samples, and the analysis was limited by the analytical sensitivity of the method. Thus, further analysis of AAs in H. cordata using analytical method of higher sensitivity is needed to alleviate public anxiety over the use of this popular vegetable. In this study, a liquid chromatography–tandem mass spectrometry (LC–MS/MS) method was used to analyze H. cordata samples for the natural existence of aristolochic acid I (AA‐I) and aristolochic acid II (AA‐II), which are the most carcinogenic and nephrotoxic compounds in the AA family. After evaluating the method performance by fortifying blank samples with three concentrations of AAs, the validated method was applied to identify AA‐I and AA‐II in both fresh and sun‐dried H. cordata samples ( n = 20) collected from different cities in China. The LC–MS/MS method achieved method detection limits (MDLs) as low as 2 ng/g of AAs in H. cordata . Analysis of the collected fresh and sun‐dried H. cordata samples revealed that AA‐I and AA‐II either do not exist naturally in H. cordata or exist at concentrations below the MDLs. Therefore, it is not very likely that consumption of H. cordata will result in AAN because AA‐I and AA‐II, the nephrotoxic and carcinogenic culprits of AAN, are not produced naturally in the plant or are produced at levels that do not pose a risk of AAN.